Children's perceptions of primary science assessment in England and Wales. (24th January 2013) - Murphy, Colette; Lundy, Laura; Emerson, Lesley; Kerr, Karen
<x xml:space="preserve">Abstract</x> This study builds on and contributes to work on assessment of children in primary school, particularly in science. Previous research has examined primary science assessment from different standpoints, but no studies have specifically addressed children's perspectives. This article provides additional insight into issues surrounding children's assessment in primary school and how the assessment of science might develop in England after the science SATs (Standard Assessment Tests) were abolished in 2009. Some research suggests that primary science assessment via SATs is a major reason for the observed decline in children's engagement with science in upper primary and lower secondary school. The analytic focus on engaging children as coresearchers to assist in the process of gathering informed views and interpreting findings from a large sample of children's views enables another contribution. The study, based on a survey of 1000 children in primary and secondary schools in England and Wales, reveals that despite being assessed under two different regimes (high‐stakes national tests in England and moderated teacher assessment in Wales), children's views of science assessment are remarkably consistent. Most appreciate the usefulness of science assessment and value frequent, non‐SATs testing for monitoring/improving science progress. There was a largely negative impact, however, of science assessment on children's well‐being, particularly due to stress. The paper demonstrates that children provide an important perspective on assessment and that including their views can improve policy‐making in relation to primary science assessment.